Optimalisasi Penggunaan Software Zoom dan Google Meet Dalam Meningkatkan Efektifitas Pembelajaran Daring - Mesran Mesran; Surya Darma Nasution; Suginam Suginam; Joli Afriany; William Ramdhan (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
Online learning or online learning can be done with the help and support of an application as a liaison between educators and students. Many educators who are still unfamiliar with the use of technology and applications, it is considered a technological gap, so it has become the duty and responsibility of computer science lecturers to provide teaching and knowledge transfer to knowledge in the use of technology and applications in assisting online learning. The transfer of knowledge was carried out by lecturers to other educators in the form of workshops, in this learning using Zoom and Google Meet software in increasing the effectiveness of online learning. Zoom and Google Meet software are the most widely used software and have advantages in their use. Learning that is taught in the form of workshops to students is expected to increase the effectiveness of learning